2023
DOI: 10.1088/1361-6471/ad10c9
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quark energy loss through polarization and radiation in the hot QCD medium

Jai Prakash,
Mohammad Yousuf Jamal

Abstract: We present a comparative study on the heavy quarks energy loss through medium polarization and gluon radiation in the quark-gluon plasma. To do so, we investigated the energy loss per unit length and drag coefficient for both cases. To have better contrast, we also obtained the nuclear modification factor employing Langevin dynamics. The comparison shows that the polarization effect dominates at lower momentum. The medium temperature also plays an important role in the comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Now, the diffusion coefficient is calculated from drag coefficients using the fluctuation-dissipation theorem, D = γET [84][85][86]. Here γ is calculated by using equation (9) as estimated in [41,87] q…”
Section: Nuclear Modification Factor R Aamentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the diffusion coefficient is calculated from drag coefficients using the fluctuation-dissipation theorem, D = γET [84][85][86]. Here γ is calculated by using equation (9) as estimated in [41,87] q…”
Section: Nuclear Modification Factor R Aamentioning
confidence: 99%
“…Physically, the soft component of energy loss corresponds to the interaction of the parton with soft collective excitations of the medium. Recent studies by the authors of [37,40,41] have demonstrated that the soft contribution to energy loss plays a vital role in the overall energy loss of the test parton within the medium and in the context of jet quenching phenomenology. The energy loss due to soft contributions can be studied through the medium polarization effect.…”
Section: Introductionmentioning
confidence: 99%